Evaluation of the Sustainability of Organizational Welfare and Human Resources to Improving Long-Term Performance - R.A, Ria Andriany; Hardy, Hardy; Asrul, Asrul; Maslim, Maslim; Megawaty, Megawaty (Paradoks : Jurnal Ilmu Ekonomi, 2025)
This study evaluates the sustainability of organizational welfare and human resource (HR) management in enhancing long-term corporate performance. It explores how sustainable HRM strategies and employee welfare policies contribute to workforce stability, engagement, and corporate resilience while aligning with Environmental, Social, and Governance (ESG) standards. This research adopts a Systematic Literature Review (SLR) approach to synthesize existing studies on HR sustainability, employee well-being, and corporate performance. The study systematically reviews academic literature from leading databases, focusing on theoretical perspectives, empirical findings, and best practices in HR sustainability and organizational welfare. The analysis identifies critical themes, trends, and research gaps to understand the topic comprehensively. The findings suggest that sustainable HR policies positively impact employee productivity, innovation, and corporate reputation. Organizations that integrate HR sustainability within their business strategies experience higher workforce engagement, lower turnover rates, and improved adaptability to industry disruptions. However, challenges persist, including the trade-off between cost efficiency and long-term workforce investment and difficulties in aligning HR sustainability with ESG frameworks and digital transformation. This study underscores the need for strategic HR investments, emphasizing continuous learning, workforce well-being, and ethical leadership. The findings provide business leaders, policymakers, and HR professionals with actionable insights to develop sustainable workforce policies that drive corporate growth, employee satisfaction, and competitive advantage.